A inserção da sustentabilidade no ensino de arquitetura e urbanismo por meio do desenvolvimento e interação de parklets para o convívio social - Russi, Rômulo do Amaral (2017)
The parklet, the focus of this dissertation, is considered a medium-sized urban furniture composed of small urban equipment. It can be designed and made, not only with reforestation or recycled woods; But also with iron, wire, resistant plastics and recycled, and these are reused after being discarded. This work has the general objective to investigate how Sustainability is being inserted in the teaching-learning course of Architecture and Urbanism with the development of ephemeral furniture. To achieve this goal, a qualitative research will be developed, through a Case Study carried out in the Architecture and Urbanism with the development of ephemeral furniture. For its development, will also be conducted Documentary Research, Direct Observation and Participant, as well as semi-structured interviews in which information will be obtained from the coordinators, teachers and students of the University course. The research pointed out the importance of the students of the Architecture and Urbanism course in thinking about the elaboration, confection and donation of sustainable furniture, providing the social interaction within the mentioned institution. The last part was applied to the students directly responsible for the elaboration of the ephemeral furniture, and, through the results indicated, it is possible to verify that 80% agree with the insertion of Sustainability within the Object Design discipline, and 88% with the professional awareness. This identification points out that, of the 30 students interviewed, 24 of them emphasize the importance of these furniture for the social life in the institution. 60% of the six teachers involved and interviewed in the course partially agree on the students' awareness of Sustainability in being a factor of great importance to think about Sustainability within the profession and that 100% of those responsible for accompanying the students were receptive Urban furniture inside the institution.